2017
DOI: 10.1002/cphc.201700716
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Imidazolate Metal–Organic Frameworks (ZIF‐8) for Electrochemical Reduction of CO2 to CO

Abstract: Metal-organic frameworks (MOFs) are regardeda sp romising materials for CO 2 adsorption,which is an importantstep in CO 2 electrochemical reduction.I nt his work, zeolitic imidazolate framework (ZIF-8) nanomaterials were synthesized with various zinc sourcesa nd used as electrocatalystsf or CO 2 reduction to CO. Among them, ZIF-8,p repared using ZnSO 4 ,d elivers the best catalytic activity towards CO 2 electroreduction,w ith 65 % CO yield. The main catalytic centerc an be attributed to the discrete Zn nodes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 32 publications
1
89
0
Order By: Relevance
“…Moreover,t he amount of products in CR-MOF electrode is 13-fold greater than the Cu electrode at À1.2 Vv ersus SHE, which could result from the increasedp rotonc onductivity,e nhanced electronic conductivity, well-defined nanopores, and the high concentration of active sites of the as-prepared MOF-based electrocatalysts. [24] They found that ZIF-8 prepared using ZnSO 4 shows the highestp erformance with aC Oy ield of 65 %. [21] In their study,H KUST-1( [Cu 3 (m 6 -C 9 H 3 O 6 ) 2 ] n ), CuAdeAce ([Cu 3 (m 3 -C 5 H 4 N 5 ) 2 ] n ), CuDTAm esoporous metal-organic aerogel( MOA) ([Cu(m-C 2 H 2 N 2 S 2 )] n ), and CuZnDTAM OA ([Cu 0.6 Zn 0.4 (m-C 2 H 2 N 2 S 2 )] n )w ere synthesized and used for CO 2 reduction in the liquid electrolyte.…”
Section: Mof Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover,t he amount of products in CR-MOF electrode is 13-fold greater than the Cu electrode at À1.2 Vv ersus SHE, which could result from the increasedp rotonc onductivity,e nhanced electronic conductivity, well-defined nanopores, and the high concentration of active sites of the as-prepared MOF-based electrocatalysts. [24] They found that ZIF-8 prepared using ZnSO 4 shows the highestp erformance with aC Oy ield of 65 %. [21] In their study,H KUST-1( [Cu 3 (m 6 -C 9 H 3 O 6 ) 2 ] n ), CuAdeAce ([Cu 3 (m 3 -C 5 H 4 N 5 ) 2 ] n ), CuDTAm esoporous metal-organic aerogel( MOA) ([Cu(m-C 2 H 2 N 2 S 2 )] n ), and CuZnDTAM OA ([Cu 0.6 Zn 0.4 (m-C 2 H 2 N 2 S 2 )] n )w ere synthesized and used for CO 2 reduction in the liquid electrolyte.…”
Section: Mof Nanoparticlesmentioning
confidence: 99%
“…However,Z n-MOF-74 generatesb oth CO and H 2 with selectivities of 15.4 %a nd 78.3 %, respectively,a tÀ0.91 V versus RHE.Z IF-8 is another Zn-based MOF that has been widely investigated and shows potentiala pplications in various fields.W ang et al synthesized ZIF-8 nanoparticles using different Zn sources, such as ZnSO 4 ,Z n(NO 3 ) 2 ,a nd Zn(AC) 2 . [24] They found that ZIF-8 prepared using ZnSO 4 shows the highestp erformance with aC Oy ield of 65 %. Their study also elucidates that the actives ites may be discrete Zn nodes in ZIF-8.…”
Section: Mof Nanoparticlesmentioning
confidence: 99%
“…[164] Ni-MIL-77 NBs are successfully applied as a non-enzymatic glucose sensor in human serum with great stability, selectivity and detection limits. [171] They found that the discrete Zn nodes exerted a critical influence for high CO selectivity. [170] Zeolitic imidazolate frameworks (ZIFs), mainly composed of Zn or Co as metal ions, is a subclass of MOFs.…”
Section: Other Monometallic Mofs and Their Compositesmentioning
confidence: 99%
“…ZIF-8 a kind of Zn-MOFs is prepared with various zinc sources by Wang et al for carbon dioxide electrochemical reduction to carbon oxide. [171] They found that the discrete Zn nodes exerted a critical influence for high CO selectivity. In another study, Kang et al selected Zn-1,3,5-benzenetricarboxylic acid MOFs (designated as Zn-BTC MOFs) to be deposited on carbon paper (CP) and act as cathodes in the electrochemical reduction of carbon dioxide.…”
Section: Other Monometallic Mofs and Their Compositesmentioning
confidence: 99%
“…This group suggested that discrete Zn nodes are critical for high CO selectivity on the basis of comparing CO 2 RR activity with Co-ZIF and annealed Zn-ZIF. [10] However, a redox process involving Zn 2 + was observed during cyclic voltammetricm easurements. By contrast, in situ X-ray absorption spectroscopy measurements and density-functional theory calculations undertaken by Jiang et al suggested that the oxidation state of Zn centers in ZIFs remainu nchanged under catalytic turnover conditions.…”
mentioning
confidence: 99%